2009
DOI: 10.1148/radiol.2512081094
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplant: Nonenhanced Renal MR Angiography with Magnetization-prepared Steady-State Free Precession

Abstract: The institutional review board approved this HIPAA-compliant study and waived informed consent. The purpose was to investigate nonenhanced magnetic resonance (MR) angiography with steady-state free precession (SSFP) with inversion recovery for assessing renal arteries in patients with renal transplants. Thirteen recipients of renal transplants underwent SSFP MR angiography before contrast material-enhanced MR angiography. Three stenoses (two mild, one severe) were identified at SSFP MR angiography in agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 26 publications
6
37
0
1
Order By: Relevance
“…The incidence of vascular complications in our study group was comparable to those reported by Liu X et al (8); graft artery thrombosis (1%), graft artery stenosis (1.5% -10%) and graft artery pseudo-aneurysm (1%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The incidence of vascular complications in our study group was comparable to those reported by Liu X et al (8); graft artery thrombosis (1%), graft artery stenosis (1.5% -10%) and graft artery pseudo-aneurysm (1%).…”
Section: Discussionsupporting
confidence: 90%
“…Our results, concerning the distribution of posttransplantation fluid collections, are comparable to Fang et al (8) in that the patients with peri-graft hematomas and urinomas were detected within the 1 st postoperative two weeks while those with lymphoceles and abscesses formation were detected at variable post-operative periods.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Magnetic reso nance angiography is increasingly used to screen for vascular abnormalities in renal allografts ( Figure 5). 41,51,53 Due to fear of nephrogenic systemic fibrosis after gadolinium-based contrast agents in patients with decreased glomerular filtration rate, imaging modalities have been developed to view the vessels without intravenous contrast. 41,44 Limitations of magnetic resonance imaging include the inability to image patients with pace makers, greater cost, lack of portability, and prolonged examination time, which is not suited to these critically ill patients.…”
Section: Clinical Manifestations Of Transplant Renal Vein Thrombosismentioning
confidence: 99%
“…A 3D gradient-echo sequence could then be initiated for angiography if contrast is used [1,29] . Table 1 displays the main findings of the studies investigating the use of MRA for the assessment of transplanted kidneys [1,[28][29][30][31][32][33][34] . The primary strength of MRA is evaluating the stenosis of relevant arteries, and the results of these studies have shown a generally good correlation of MRA with digital subtraction angiography (DSA), which is the golden standard for vascular abnormalities.…”
Section: Mr Nephro-urography/renographymentioning
confidence: 99%